Kemampuan Jenis PGPR dalam Menekan Serangan Nematoda Puru Akar (Meloidogyne spp.) pada Tanaman Seledri (Apium graveolens L.) - Siti Hadijah; Elly Liestiany; Noor Aidawati (www.ulm.ac.id, 2023)
Celery plant (Apium graveolens L.) is a cultivated plant that has high economic value, usually used as food flavoring, cooking seasoning and can also be used as a dish garnish. Functions for health such as drugs to lower high blood pressure for people with hypertension. One pest that can affect the quality and quantity of celery production is root knot nematode (NPA) caused by Meloidogyne spp. This study aims to determine the ability of PGPR species to suppress root knot nematodes (Meloidogyne spp.) on celery. This study was designed using a one-factor Completely Randomized Design (CRD). The factor tested was the effect of giving PGPR types namely elephant grass root, kalakai root, fern root and bamboo root. There were 5 treatments and 4 replications. The results showed that giving PGPR could reduce the intensity of root knot attacks and reduce nematode populations in the soil around the roots, as well as significantly affect the number of leaves (stalks) of celery at the age of 58 and 72 days after planting (dap) and weight. wet celery at the age of 44, 58 and 72 dap.